Answer:
![P(A)= 0.48, P(B)= ?, P(A \cap B)= 0.21, P(A \cup B) =0.89](https://img.qammunity.org/2021/formulas/mathematics/high-school/ezjht8ls4eqsxpjoxdlfwvcy3xtu14e6wj.png)
And for this case we can use the total rule of probability given by:
![P(A \cup B) = P(A) +P(B) -P(A\cap B)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7c5l6l2us7zy45cl2ngv2grkn8dqq6vjin.png)
And if we solve for
we got:
![P(B)= P(A \cup B) -P(A) +P(A \cap B)](https://img.qammunity.org/2021/formulas/mathematics/high-school/msdhcjr7lpnawqek85idtp1lyqs7ksw7hn.png)
And replacing we got:
![P(B) = 0.89 -0.48 +0.21= 0.62](https://img.qammunity.org/2021/formulas/mathematics/high-school/uxvjfkewgan4xu8n55ihg0sqo4j90yvy0l.png)
Explanation:
We have the following probabilities given:
![P(A)= 0.48, P(B)= ?, P(A \cap B)= 0.21, P(A \cup B) =0.89](https://img.qammunity.org/2021/formulas/mathematics/high-school/ezjht8ls4eqsxpjoxdlfwvcy3xtu14e6wj.png)
And for this case we can use the total rule of probability given by:
![P(A \cup B) = P(A) +P(B) -P(A\cap B)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7c5l6l2us7zy45cl2ngv2grkn8dqq6vjin.png)
And if we solve for
we got:
![P(B)= P(A \cup B) -P(A) +P(A \cap B)](https://img.qammunity.org/2021/formulas/mathematics/high-school/msdhcjr7lpnawqek85idtp1lyqs7ksw7hn.png)
And replacing we got:
![P(B) = 0.89 -0.48 +0.21= 0.62](https://img.qammunity.org/2021/formulas/mathematics/high-school/uxvjfkewgan4xu8n55ihg0sqo4j90yvy0l.png)